Assessing performance of SMEs in the tourism industry through intellectual capital and corporate entrepreneurship: a conceptual framework / Ahmad Rusydan Ab Kadir ... [et al.] - Ab Kadir, Ahmad Rusydan; Ngah, Rohana; Salleh, Zarina; Sulaiman, Joehary (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2018)
The tourism industry is an important service sector of the Malaysian economy and has been identified as one of the major contributors of the country's economic success. Malaysia is one of the top ranked countries in the world for tourist arrival. Currently, the government has targeted to achieve the arrival of 36 million tourists that will generate up to RM168 billion in tourist receipts for the country by 2020. However, the tourism industry is facing the high arrival low yield issue where yield per tourist in Malaysia is lower as compared to its neighbouring countries. Lower yield was caused by shorter stays and lack of spending on tourism products and services. Tourist arrival and spending affect the performance of firms involves in tourism industry especially the SMEs. Since SMEs are the biggest players in the tourism industry, it is important to explore more on the issues on how SMEs in tourism industry can use their limited resources especially their intangible resources as well as harnessing their entrepreneurial capabilities in order to improve performance. This paper presents the current research on intellectual capital and corporate entrepreneurship in achieving better performance of SMEs in tourism industry in Malaysia. It focuses on two main questions: How intellectual capitals boost performance of SMEs in tourism industry? and How corporate entrepreneurship enhances performance of SMEs in tourism industry?